Addicts vs mental health users with personality disorders: its relation to quality of life in Axis I psychopathology, psychological adjustment and family dynamics. - Martínez-González, José Miguel; Munera-Ramos, Pilar; Becoña-Iglesias, Elisardo (Anales de Psicología / Annals of Psychology, 2013)
The aim of this study was to analyze some variables of great relevance in the treatment of personality disorders such as quality of life, the severity level of psychological adjustment, the concomitant Axis I psychopathology and perception of family dynamics of these patients. The sample is composed of 68 patients with a personality disorder of which 57.4% are drug addicts undergoing treatment in an outpatient drug addiction center and 42.6% are users of a mental health clinic has not addictive disorders. The results showed no significant differences in life quality or severity of psychological adjustment among patients on the basis of drug addiction. The differences appear to be linked to the concomitance of psychopathology on Axis I, because for those who do not have a quality of life higher and better psychological adjustment. This indicates that the presence of Axis I psychopathology, in patients with personality disorders, increases the difficulty associated with treating these patients. In terms of family dynamics has been shown that while the attachment has a negative impact on quality of life of these patients, family resources the better. It seems that the perceived quality of life in patients with personality disorders, drug or mental health consumers, is determined by the concomitant presence of other psychopathology on Axis I. This concomitant should be targeted for therapeutic intervention.